A new kind of McKay correspondence from non-Abelian gauge theories - Lerche, Wolfgang; Mayr, Peter; Walcher, Johannes (Arxiv, 2001)
The boundary chiral ring of a 2d gauged linear sigma model on a K\"ahler manifold $X$ classifies the topological D-brane sectors and the massless open strings between them. While it is determined at small volume by simple group theory, its continuation to generic volume provides highly non-trivial information about the $D$-branes on $X$, related to the derived category $D^\flat(X)$. We use this correspondence to elaborate on an extended notion of McKay correspondence that captures more general than orbifold singularities. As an illustration, we work out this new notion of McKay correspondence for a class of non-compact Calabi-Yau singularities related to Grassmannians.